2013
DOI: 10.1021/jp312658q
|View full text |Cite
|
Sign up to set email alerts
|

Examining Hysteresis in Composite xLi2MnO3·(1–x)LiMO2 Cathode Structures

Abstract: This paper reports the results of an initial investigation into the phenomenon of hysteresis in the charge−discharge profile of high-capacity, lithiumand manganese-rich "layered−layered" xLi 2 MnO 3 •(1−x)LiMO 2 composite cathode structures (M = Mn, Ni, Co) and "layered−layered-spinel" derivatives that are of interest for Li-ion battery applications. In this study, electrochemical measurements, combined with in situ and ex situ X-ray characterization, are used to examine and compare electrochemical and structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
275
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(299 citation statements)
references
References 69 publications
23
275
1
Order By: Relevance
“…As oxygen release is hypothesized to be correlated to the voltage hysteresis and the hysteresis between charge and discharge, 11,45 one might pose the question whether the large differences in oxygen release shown in Figure 3 also have such a big influence onto the voltage fading of the different materials. The mean charge and discharge voltages are shown in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As oxygen release is hypothesized to be correlated to the voltage hysteresis and the hysteresis between charge and discharge, 11,45 one might pose the question whether the large differences in oxygen release shown in Figure 3 also have such a big influence onto the voltage fading of the different materials. The mean charge and discharge voltages are shown in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the oxygen release is a side reaction occurring at the HE-NCM nearsurface region, 25 while reversible and irreversible transition metal migration in the bulk material cause the main voltage fading and the high hysteresis. 35,45,46 Figure 5 depicts the dQ/dV plots for cycle 3, cycle 20, and cycle 48 extracted from the cycling data shown in Figure 4. Hereby, cycle 3 is the first C/5 cycle between 2.0 V and 4.7 V and therefore is subjected to the same cycling conditions as cycle 20 and 48.…”
Section: Resultsmentioning
confidence: 99%
“…The primary experiments are electrochemical; and often times extracting information on voltage fade phenomena relies on an interpretation of the voltage profile as a function of the number of charge/discharge cycles. Secondary experiments such as X-ray absorption fine structure spectroscopy, 4,11 X-ray diffraction, 4,11 Li nuclear magnetic resonance spectroscopy, 12 neutron diffraction, 8 and transmission electron microscopy, 5 can provide valuable information on cathode structure during the evolution of voltage fade phenomena. These studies provided evidence for a correlation between transition metal migration and voltage fade; leading to a qualitative mechanism of voltage fade as outlined in Ref.…”
mentioning
confidence: 99%
“…Croy et al have reported a correlation between voltage fade and hysteresis in the charge/discharge profiles. 6,7 The layered electrode materials such as 0.5Li 2 MnO 3 · 0.5LiMn 0.375 Ni 0.375 Co 0.25 O 2 exhibit a significant hysteresis loop, which is considerably different from other traditional lithium insertion electrode materials. 6 To account for this hysteresis, both the reversible and irreversible migration of transition metal ions were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The layered electrode materials such as 0.5Li 2 MnO 3 · 0.5LiMn 0.375 Ni 0.375 Co 0.25 O 2 exhibit a significant hysteresis loop, which is considerably different from other traditional lithium insertion electrode materials. 6 To account for this hysteresis, both the reversible and irreversible migration of transition metal ions were proposed. 7 Studies in the literature have so far revealed several important factors for the capacity fade of the layered materials, which include the dissolution of Mn ions into electrolytes, 8 the decomposition of electrolytes through side reactions of LiPF 6 with water molecules, 9 and structural transformations to, e.g.…”
Section: Introductionmentioning
confidence: 99%